2001
DOI: 10.1577/1548-8659(2001)130<0501:tsoctm>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Calcein to Mark Poeciliid Fish and a New Method of Detection

Abstract: The suitability of calcein as a marker for population studies depends on (1) the assumption that marked individuals have unaltered viability, (2) the fidelity of the calcein label, and (3) the facility with which calcein can be used. We examined the effects of calcein on survival, growth, and the timing and size at sexual maturity of least killifish Heterandria formosa and present a new method for detecting calcein. To test the assumption that marked individuals have unaltered viability, juvenile least killifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 14 publications
5
52
2
Order By: Relevance
“…Immersion marking with fluorochrome dyes involves a compromise between cost, concentration, immersion time, salinity, mortality, growing conditions, and mark retention to produce the best mark [19]. In the present study, juvenile grass carp were successfully marked by immersion in 50-200 mg/l CAL or 150-300 mg/l ARS for 24 h. With the exception of non-lateral line scales from the 150 mg/l ARS treatment group and lateral line scales Our results further agree with other similar studies demonstrating that CAL and ARS are effective chemical markers for immersion marking which can be used in biological research and for the evaluation of stock enhancement programs (e.g., Baer and Rösch [27]; Leips et al [30]; Walt and Faragher [32]). …”
Section: Immersion Marking Applicationsupporting
confidence: 91%
See 2 more Smart Citations
“…Immersion marking with fluorochrome dyes involves a compromise between cost, concentration, immersion time, salinity, mortality, growing conditions, and mark retention to produce the best mark [19]. In the present study, juvenile grass carp were successfully marked by immersion in 50-200 mg/l CAL or 150-300 mg/l ARS for 24 h. With the exception of non-lateral line scales from the 150 mg/l ARS treatment group and lateral line scales Our results further agree with other similar studies demonstrating that CAL and ARS are effective chemical markers for immersion marking which can be used in biological research and for the evaluation of stock enhancement programs (e.g., Baer and Rösch [27]; Leips et al [30]; Walt and Faragher [32]). …”
Section: Immersion Marking Applicationsupporting
confidence: 91%
“…Immersion marking fish with fluorochrome dyes is widely used to evaluate stock enhancement programs (e.g., Barker and Mckaye, [12]; Lagardère et al [21]); however, the dye concentrations and immersion times that yield optimal results differs between species [30]. In this study, the methods of mark detection were similar in the sagittae, scales (including non-lateral line and lateral line scales), and fin rays.…”
Section: Mark Qualitymentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, mortality resulted greater than in other similar studies (Leips et al 2001, Bashey 2004, Crook et al 2007, Crook et al 2009). Size of fish could be an explanation of these results since, in those studies, fish were smaller and we observed that small fish were less vulnerable to the osmotic immersion shock.…”
Section: Discussioncontrasting
confidence: 58%
“…Calcein (C 30 H 26 N 2 O 13 ) is a fluorochrome that binds to calcium and becomes incorporated in calcified structures of growing animals when exposed to this chemical agent, and has been successfully used in ecological studies of several marine species (Moran 2000). Immersion in a calcein solution leaves a fluorescent mark in calcified structures, which is visible under epifluorescent microscopy and has been used to identify marked individuals and to estimate growth rates in several organisms, including fishes (Wilson et al 1987, Leips et al 2001, Frenkel et al 2002, ascidians (Lambert and Lambert 1996), molluscs (Kaehler and McQuaid 1999, Moran 2000, Van der Geest et al 2011, echinoderms Urbaniak 2004, Ebert et al 2008) and crustaceans (Helms 2004, Kilada et al 2012.…”
Section: Introductionmentioning
confidence: 99%